(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
Objective. Describe two cardiovascular risk indicators (CVR), in a university population for 4 years. Material and method. A retrospective descriptive study is carried out during 4 years of blood pressure and abdominal perimeter in the university community. Variables in average, standard deviation and confidence intervals were described, a comparative analysis was made by sex; analysis of variance and Chi square were performed and a value of p <0.05 was considered for statistically significant differences. Results. On average 402 people participated semiannually, 66.57% students, 17.57% administrative, 7.18% teachers and other 7.03%. Women 46.01% and men 53.99%. The average age was 28.79 years. The average abdominal perimeter was 82.37 centimeters and the blood pressure 113/73 on average. Statistically significant relationships were found in student participation is mostly male with 36.91% and 29.63% female. And the administrative staff is mostly female with 10.26% and male 7.31%. The average abdominal perimeter presents a progressive increase and a statistically significant relationship (value of p <0,05) with age, sex and status. A statistically significant relationship was found with sex, age and systolic and diastolic blood pressure (p value <0,05). Discussion and conclusion. The abdominal perimeter and blood pressure are on average in normal limits, however, the abdominal perimeter increases progressively and 15.9% CVR was found in the university community with these indicators.